A new species of the genus Lecanopsis Targioni Tozzetti, 1868 (Hemiptera: Coccoidea: Coccidae) from the Italian peninsula: description and remarks on its life history (Bollettino di zoologia agraria e bachicoltura, 2024)
A new species of coccoid, living on the roots of Gramineae, was found on Monte Sirino (Basilicata region, in southern Italy) and in Val Fondillo (Abruzzo region, in southern Italy). The new species is named Lecanopsis pellizzariae n. sp.. The most obvious characters of the new species are the non-minaret-like shape of the last marginal seta of the 1st-instar, the presence of well-developed legs in the 3rd-instar females and also, in comparison with other species of the genus Lecanopsis Targioni Tozzetti, 1968, the unusual increase in body size of the adult female, because of their feeding activity. All known life stages of Lecanopsis pellizzariae n. sp. live on stolons of Gramineae under stones. Young and small females are present in May while mature ones occur in June. Females feed on the host plant for the duration of their life cycle and enlarge in each life stage. Second instar females are present until the end of September; later, only 2nd-instar males and 3rd-instar females are present. These latter two life stages overwinter. Adult males, as well as pupal instars are unknown but second instar males are common.
Keywords: Coccidae; Lecanopsis pellizzariae n. sp.; morphology; life history